Ethics Certification of Health Information Professionals - Kluge, Eike-Henner; Lacroix, Paulette; Ruotsalainen, Pekka (Yearbook of Medical Informatics, 2018)
Objectives: To provide a model for ensuring the ethical acceptability of the provisions that characterize the interjurisdictional use of eHealth, telemedicine, and associated modalities of health care delivery that are currently in place.Methods: Following the approach initiated in their Global Protection of Health Data project within the Security in Health Information Systems (SiHIS) working group of the International Medical Informatics Association (IMIA), the authors analyze and evaluate relevant privacy and security approaches that are intended to stem the erosion of patients' trustworthiness in the handling of their sensitive information by health care and informatics professionals in the international context.Results: The authors found that while the majority of guidelines and ethical codes essentially focus on the role and functioning of the institutions that use EHRs and information technologies, little if any attention has been paid to the qualifications of the health informatics professionals (HIPs) who actualize and operate information systems to deal with or address relevant ethical issues.Conclusion: The apparent failure to address this matter indicates that the ethical qualification of HIPs remains an important security issue and that the Global Protection of Health Data project initiated by the SiHIS working group in 2015 should be expanded to develop into an internationally viable method of certification. An initial model to this effect is sketched and discussed.
Keywords: Ethics; health informatics professionals; certification